2016
DOI: 10.1186/s12864-015-2352-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs and their targets by high-throughput sequencing and degradome analysis in cytoplasmic male-sterile line NJCMS1A and its maintainer NJCMS1B of soybean

Abstract: BackgroundCytoplasmic male sterility (CMS) provides crucial breeding materials that facilitate hybrid seed production in various crops, and thus plays an important role in the study of hybrid vigor (heterosis), in plants. However, the CMS regulatory network in soybean remains unclear. MicroRNAs (miRNAs) play crucial roles in flower and pollen development by targeting genes that regulate their expression in plants. To identify the miRNAs and their targets that exist in the soybean CMS line NJCMS1A and its maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 75 publications
(83 reference statements)
2
38
2
Order By: Relevance
“…The most studied model for viral infections in birds is Marek's disease, which is a consequence of a Herpesvirus infection in poultry. Publications linked to Marek's disease addressed virus encoded miRNAs (Morgan et al, 2008;Yao et al, 2008;Zhao et al, 2009;Muylkens et al, 2010;Luo et al, 2011;Xu et al, 2011;Zhao et al, 2011;Coupeau et al, 2012;Strassheim et al, 2012), changes in host miRNA expression during infection (Yao et al, 2008;Lambeth et al, 2009a;Xu et al, 2010;Tian et al, 2012;Stik et al, 2013;Dinh et al, 2014;Li et al, 2014b;Li et al, 2014c;Lian et al, 2015a;Lian et al, 2015b;Han et al, 2016), or attempts to block the virus with RNAi Chen et al, 2009b;Lambeth et al, 2009b). A similar set of articles has been found for other studied viruses infecting birds -e.g.…”
Section: Antiviral Defense -Interferon Response and Crosstalk With Rnmentioning
confidence: 99%
See 1 more Smart Citation
“…The most studied model for viral infections in birds is Marek's disease, which is a consequence of a Herpesvirus infection in poultry. Publications linked to Marek's disease addressed virus encoded miRNAs (Morgan et al, 2008;Yao et al, 2008;Zhao et al, 2009;Muylkens et al, 2010;Luo et al, 2011;Xu et al, 2011;Zhao et al, 2011;Coupeau et al, 2012;Strassheim et al, 2012), changes in host miRNA expression during infection (Yao et al, 2008;Lambeth et al, 2009a;Xu et al, 2010;Tian et al, 2012;Stik et al, 2013;Dinh et al, 2014;Li et al, 2014b;Li et al, 2014c;Lian et al, 2015a;Lian et al, 2015b;Han et al, 2016), or attempts to block the virus with RNAi Chen et al, 2009b;Lambeth et al, 2009b). A similar set of articles has been found for other studied viruses infecting birds -e.g.…”
Section: Antiviral Defense -Interferon Response and Crosstalk With Rnmentioning
confidence: 99%
“…Thus, if there are mRNAs cleaved by a miRNA after its 10 th nucleotide, one would observe alignment of RNA termini matching the predicted miRNA binding site. Degradome analysis usually defines a category of transcripts predicted to be endonucleolytically cleaved and then are cleavage positions compared to predicted miRNA binding sites (Li and Sunkar, 2013;Xing et al, 2014;Ding et al, 2016;Fan et al, 2016;Wang et al, 2016). Degradome analysis and target prediction has been integrated in to a web resource comPARE for plant miRNA target analysis (Kakrana et al, 2014).…”
Section: Degradome Analysismentioning
confidence: 99%
“…Experiment results revealed that miRNAs assist to regulate MS and fertility restoration. In soybean, miRNA sequencing based on high‐throughput sequencing and by degradome analysis, a CMS line NJCMS1A and its maintainer NJCMS1B was archived successfully (Ding et al, ). The result also showed whilst regulating MS, some miRNA also target other elements and help to identifying them such as MADS‐box transcription factor, NADP‐dependent isocitrate dehydrogenase and NADH‐ubiquinone oxidoreductase 24 kDa subunit.…”
Section: Molecular Mechanisms Of Male Sterility In Soybeanmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of non-coding endogenous ~21 nt small RNAs (Bartel et al 2004) that play vital regulatory roles in plant growth and development, such as flowering-time regulation (Nie et al 2015), heat tolerance (Liu et al 2017a), accumulation of anthocyanins (Liu et al 2017b), response to the phytohormone abscisic acid (Duan et al 2016), cotton fiber elongation (Wang et al 2016b), pollen or flower bud development (Shen et al 2011; Yang et al 2013; Jiang et al 2014; Ding et al 2016; Zhang et al 2016), and so on. Among all of the miRNA families, MIR156 is one of the most conserved families in plants (Wang et al 2016c) and regulates the vegetative phase change floral transition, integrated into flowering pathways by target squamosa promoter binding protein-like (SPL) transcription factors (Spanudakis et al 2014).…”
Section: Introductionmentioning
confidence: 99%